1991
DOI: 10.1016/0031-9384(91)90574-8
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-running activity rhythms in two inbred strains of laboratory rats under different photoperiods

Abstract: SIEBERT, U. AND F. WOLLNIK. Wheel-running activity rhythms in two inbred strains of laboratory rats under different photoperiods. PHYSIOL BEHAV 50(6) 1137-1143, 1991.-Wheel-running activity patterns were studied in two inbred rat strains (ACI/Ztrn and LEW/Ztm) under 24-h light-dark cycles with various pbotoperiods. The ACI strain was characterized by a unimodal activity pattern, whereas the LEW strain exhibited a multimodal activity pattern consisting of two activity bouts about 3-5 h apart. Harmonic spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Previous investigations of LEW rats suggest that the unusual activity pattern of this strain is caused by a distinct coupling of multiple circadian oscillators (34,46,47). However, the neurophysiological or neurochemical mechanisms underlying the unusual activity pattern of the LEW strain are still unknown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous investigations of LEW rats suggest that the unusual activity pattern of this strain is caused by a distinct coupling of multiple circadian oscillators (34,46,47). However, the neurophysiological or neurochemical mechanisms underlying the unusual activity pattern of the LEW strain are still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…These strains have rather unusual activity patterns that may be caused by multiple circadian oscillators coupled to each other with a phase relationship of 4-6 h (34,(46)(47)(48). The goal of the study was to investigate the effects of various antidepressant drugs on the circadian wheelrunning rhythms of the two strains compared to strain ACI, which shows an activity pattern found in most laboratory rats.…”
mentioning
confidence: 99%
“…2), but were nearly completely absent in rats [26], which unlike hamsters, are minimally responsive to seasonal variations in day length [27]. …”
Section: Discussionmentioning
confidence: 99%
“…These highly synchronizing conditions could account for the absence of a differentiated development. The study by Siebert and Wollnik (1991) has indicated that in rats 3-6 weeks of age, the phase relationship between individual activity bouts may be modified by LD cycles of different photoperiods; this modification was not observed in adults. This experiment thus demonstrated the fragility and plasticity of the system at an early stage.…”
Section: Discussionmentioning
confidence: 91%